2019
DOI: 10.1001/jamanetworkopen.2019.9144
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Severity of Sesame Allergy in the United States

Abstract: Key Points Question What is the current population-level burden of sesame allergy in the United States? Findings Using a cross-sectional population-based survey, an estimated 0.49% of the US population reported a current sesame allergy, whereas 0.23% of the population had a convincing sesame allergy using confirmatory symptom report criteria. Meaning The findings suggest that sesame allergy is a relatively common, frequently como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 28 publications
3
45
0
1
Order By: Relevance
“…Among individuals with convincing sesame allergy, 62.2% reported a current epinephrine prescription. 5 This rate is comparable to reports of children 1 and adults 6 with peanut allergy. Among those with epinephrine, approximately 33.7% with sesame allergy had used the device at least once in their lifetime.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Among individuals with convincing sesame allergy, 62.2% reported a current epinephrine prescription. 5 This rate is comparable to reports of children 1 and adults 6 with peanut allergy. Among those with epinephrine, approximately 33.7% with sesame allergy had used the device at least once in their lifetime.…”
supporting
confidence: 81%
“…Concerningly, one-half of children and one-third of adults with sesame allergy reported that they did not have a physician diagnosis of their allergy. 5 However, severe reactions involving multiple systems were reported by one-third of the population with convincing sesame allergy. Esophageal eosinophilia and food protein-induced enterocolitis were more common in individuals with sesame allergy, compared with individuals with other food allergies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A second study shows prevalence of sesame allergy in the USA at 0.23-0.49% [2]. 8 April, FASTER Act introduced in USA; it proposes to regulate sesame as an allergen [44].…”
Section: Milestonementioning
confidence: 99%
“…There is sound evidence that the Western world is in the midst of an ongoing widespread food allergy, and that some of the Eastern world is noticing its rise as well [1][2][3][4]. For example, recent reports show that the prevalence of food allergies in the United States of America (USA) have increased to 8% in children and 10.8% among adults from their respective prevalence rates of 6% and 3.7% just 15 years ago [5,6].…”
Section: Introductionmentioning
confidence: 99%